Epidemiological evaluation of Leishmania infantum zoonotic transmission risk in the recently established endemic area of Northwestern Italy. (10th May 2018) - Ferroglio, E.; Battisti, E.; Zanet, S.; Bolla, C.; Concialdi, E.; Trisciuoglio, A.; Khalili, S.; Biglino, A.
Summary: Leishmania infantum infection had been expanding into new areas due to changes in vector and host biology. Zoonotic visceral leishmaniasis has become endemic in previously unsuitable areas as vectors find favourable climatic conditions and an increasing number of reservoir dogs are moved between traditionally and new endemic areas. Monitoring vector and disease expansion in areas of recent colonization is needed to understand transmission mechanisms and patterns of disease establishment. Here, we studied the infection status of 815 human blood donors and of 803 sympatric dogs from five, newly endemic, areas in Northwestern Italy. In autochthonous dogs, the seroprevalence of anti‐ L. infantum antibodies, recorded by Western blot, reached 42.22%, while in humans, the seroprevalence was of 16.81%. No significant correlation between the infection status of dogs and that of their human owners was found, but L. infantum infection was recorded in the different study areas with significant levels of diversity. Restriction fragment length polymorphism showed a high genetic variability of the circulating strains and gave useful insights on patterns of disease establishment into a naïve area.